(untitled) (The International Journal for Scientific Research, 2025)
This research addresses Chad’s historic decision in November 2024 to terminate its military cooperation agreement with France—a move that marks a significant shift in the bilateral relations between the two countries. The study examines the historical context of Franco-Chadian military relations from the colonial era to the termination of the agreement. It analyzes the motives behind the decision in light of rising anti-French sentiment across Africa, particularly in the Sahel region. The research also discusses the implications at national, regional, and international levels, including the security and strategic challenges facing Chad. Furthermore, it outlines a new vision for building alternative partnerships that reinforce national sovereignty and align with the country’s security and development priorities.